2023
DOI: 10.1021/acs.nanolett.3c00146
|View full text |Cite
|
Sign up to set email alerts
|

Direct Photo-Patterning of Efficient and Stable Quantum Dot Light-Emitting Diodes via Light-Triggered, Carbocation-Enabled Ligand Stripping

Abstract: Next generation displays based on quantum dot light-emitting diodes (QLEDs) require robust patterning methods for quantum dot layers. However, existing patterning methods mostly yield QLEDs with performance far inferior to the state-of-the-art individual devices. Here, we report a light-triggered, carbocation-enabled ligand stripping (CELS) approach to pattern QLEDs with high efficiency and stability. During CELS, photogenerated carbocations from triphenylmethyl chlorides remove native ligands of quantum dots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…The variations in solubility of the light-exposed region are enabled by a small amount of PAG additive (1–2 wt %), which is beneficial for both photoluminescence (PL) down-conversion and electroluminescence (EL) applications. Recently, Fu et al employed PAG-based direct optical lithography to fabricate patterned high-efficiency CdSe-based QD LEDs …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The variations in solubility of the light-exposed region are enabled by a small amount of PAG additive (1–2 wt %), which is beneficial for both photoluminescence (PL) down-conversion and electroluminescence (EL) applications. Recently, Fu et al employed PAG-based direct optical lithography to fabricate patterned high-efficiency CdSe-based QD LEDs …”
mentioning
confidence: 99%
“…In our previous study, we reported that an addition of 2 wt % PAG can reduce the PLQY of CdSe-based core/shell QDs by ∼30%. Although recent studies have attempted to address this issue, ,, it has not been completely overcome. In particular, the aforementioned issue is observed to be more critical in the case of InP-based QDs .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…61−63 As shown in Figure 2d f). 64 In addition, QDs possess excellent stability in ambient conditions, which is conducive to the extension of service life. More recently, perovskite LEDs (PeLEDs) based on metallic halide perovskites (MHPs) have also been thriving in the field of optoelectronics (Figure 2g).…”
mentioning
confidence: 99%
“…Therefore, an additional encapsulation procedure is critical for luminescence duration. Apart from OLEDs, quantum dot LEDs (QLEDs) are another powerful display technology in virtue of the high color purity, stability and quantum efficiency of QD emitters. As shown in Figure d, QDs usually have core–shell structures and their surfaces are passivated by organic ligands, thus facilitating their dispersion in nonpolar solvents and the large-scale production of QLEDs (Figure e–f) . In addition, QDs possess excellent stability in ambient conditions, which is conducive to the extension of service life.…”
mentioning
confidence: 99%